Ethics of socioeconomics : criticial observations on capitalism through the lens of a lawyer - Byttebier, K. (Koen) (Economic and financial law & policy (shifting insights & values) ;, 2024)
The book analyzes socioeconomic through the lens of a lawyer. In the past decade the world has witnessed some severe financial and economic crises, especially the financial crisis of 2007-2008 and the crisis caused by the COVID-19 pandemic. The author states that the socio-economic order has in the past four to five decades been thoroughly redesigned, generally favouring models that prioritize the free market over the public interest or even, more generally, government operation. He works out that during four to five decades, globalized, capitalist societies are facing a multiplicity of fundamental problems, such as: (1) increasing debt that severely burdens both the private and public sectors; (2) persistent poverty and an ever-increasing polarization between rich and poor, in addition to (3) intractable environmental problems that, fifty years after the Club of Rome's report entitled Limits to growth (1972), has dragged the world into what in recent years has been referred to as "climate change." The book explains why all this is the direct result of value choices made from the late Middle Ages onwards, when in the Western world the societal models of that time were increasingly abandoned for a societal model that came to rely on the primacy of economic interests. The book not only subjects the ethical choices but also examines various problems it has caused and probes for possible ways out. This is an open access book